Preparation of two-dimensional nano graphene sheet and application of two-dimensional nano graphene sheet in water-based drilling fluid

Two-dimensional nanographene sheets prepared through green chemical peeling technology are used in water-based drilling fluid, which solves the problem of instability of the well wall in shale gas exploration, achieves efficient sealing and stability improvement, replaces oil-based drilling fluid, and reduces the Environmental impact.

CN119240680APending Publication Date: 2025-01-03SOUTHWEST PETROLEUM UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411366452.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing water-based drilling fluid is prone to agglomeration and insufficient pressure bearing capacity in shale gas exploration, and the sealing effect is not ideal, making it difficult to replace oil-based drilling fluid. The nanographene sheets have poor dispersion in high temperature and high mineralization environments, resulting in The problem of instability of the well wall.

Method used

The two-dimensional nanographene sheets were prepared by green chemical peeling technology. The raw material graphite was mixed with the activator, and the oxidizing agent was carried out and ultrasonic treatment was carried out to prepare high-quality two-dimensional nanographene sheets, and the surface modification was used to improve their high mineralization. Dispersibility in the environment, used as sealant in water-based drilling fluid.

Benefits of technology

The effective sealing of two-dimensional nanographene sheets in the shale gas formation is achieved, which improves the stability of the well wall, delays the transfer of pore pressure, significantly improves drilling efficiency, and reduces the impact on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240680A_ABST
    Figure CN119240680A_ABST
Patent Text Reader

Abstract

The invention relates to the field of oilfield chemistry, and discloses preparation of a two-dimensional nano-graphene sheet and application of the two-dimensional nano-graphene sheet in water-based drilling fluid, and the preparation method of the two-dimensional nano-graphene sheet comprises the following steps: (1) uniformly mixing raw materials of graphite and an activator, and carrying out a first reaction to obtain an activated graphite dispersion liquid; (2) slowly adding an oxidizing agent into the activated graphite dispersion liquid, heating in a temperature-controlled water bath, and keeping the temperature for a certain time to obtain a two-dimensional nano graphene sheet pre-product; and (3) cleaning the graphene pre-product with deionized water until the graphene pre-product is neutral, and carrying out ultrasonic treatment in the deionized water to obtain the two-dimensional nano graphene sheet dispersion liquid. The two-dimensional nano graphene sheet dispersion liquid is good in dispersity in the water-based drilling fluid, high in pressure bearing capacity and capable of blocking nano-scale pores, delaying pore pressure transmission, improving the stratum pressure bearing capacity and improving the rheological property of the drilling fluid and the well wall stability at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patent invention relates to the field of oilfield chemistry, specifically to a green chemical preparation method for two-dimensional nanographene sheets and their application in water-based drilling fluids. Background Art

[0002] The world's energy development has entered a critical period of transformation from fossil energy to new energy. Natural gas, as the cleanest fossil energy, is the "bridge" and the best "partner" for the transformation from fossil energy to new energy. As one of the forms of natural gas in nature, shale gas has enriched the types of its exploration and development, expanded the exploration field and expanded the exploration range. However, shale gas high-quality reservoir sections have a large number of micro-nanoscale cracks and pores, and complex downhole accidents such as wellbore instability often occur during drilling, which seriously hinders the drilling and development of shale gas. Oil-based drilling fluid is the preferred system for drilling shale gas formations, but its promotion and application are limited due to its poor environmental protection and high preparation cost. Exploring a high-performance water-based anti-collapse drilling fluid system that can replace oil-based drilling fluid has become a key technology for efficient drilling and development of shale gas resources, and it is also a global engineering and technical problem.

[0003] One of the key points to achieve the successful transformation of oil-based drilling fluid to water-based drilling fluid is to effectively plug the micro-nanoscale cracks and pores in the shale formation to avoid the instability of the wellbore caused by the filtrate penetrating into the shale formation. Two-dimensional nanographene sheets (Graphene Nanosheets) have extremely high mechanical strength and toughness, can maintain structural stability under high pressure conditions, are not easy to break, and can effectively prevent fluid penetration. It has great potential as a shale plugging material, but the current method for large-scale preparation of two-dimensional nanographene sheets mainly follows the "top-down" preparation idea, that is, natural graphite is peeled off into two-dimensional nanographene sheets with the help of external force. The redox method that follows one of the "top-down" preparation ideas has been used earlier by people to peel off two-dimensional nanographene sheets, but the quality of the prepared two-dimensional nanographene sheets is poor, the preparation process is complicated, and corrosive strong acids are inevitably used in the preparation process, which has a high risk factor. Although the mechanical exfoliation methods (liquid phase exfoliation and ball milling exfoliation) developed subsequently can successfully exfoliate graphite into a few-layer two-dimensional nanographene sheets, the number of layers of the obtained two-dimensional nanographene sheets cannot be controlled, and the size of the prepared two-dimensional nanographene sheets is very small.

[0004] To this end, with the goal of developing green chemical exfoliation technology for two-dimensional nanographene sheets, it is imperative to explore preparation methods with simple steps, low cost and easy scalability to promote the practical application of two-dimensional nanographene sheets. In addition, in the drilling of shale gas formations, since the water-based drilling fluid is in extreme environments such as high temperature and high mineralization, the stable dispersion ability of the two-dimensional nanographene sheets will be seriously damaged, resulting in agglomeration and precipitation in the shale formation environment. Therefore, the core technology of this patent invention is to successfully prepare two-dimensional nanographene sheets using green chemical exfoliation technology, achieve effective plugging of low-permeability pores in shale and the practical application of nanomaterials in water-based drilling fluids, and promote the successful transformation of oil-based drilling fluids to water-based drilling fluids in shale mining. Summary of the invention

[0005] The present invention aims to solve the problems of easy agglomeration, insufficient pressure bearing capacity and unsatisfactory plugging effect faced by existing water-based drilling fluid plugging materials in shale gas formation applications. To this end, the present invention proposes a two-dimensional nanographene sheet prepared based on green chemical exfoliation technology and its application in water-based drilling fluid.

[0006] The core of the present invention is to develop a simple, economical and easy-to-scale green chemical exfoliation method to successfully prepare high-quality two-dimensional nanographene sheets. This nanographene sheet has extremely high mechanical strength and stability, and can effectively block micro-nanoscale cracks and pores in the high temperature and high pressure environment of shale gas formations, preventing the instability of the well wall caused by filtrate penetration.

[0007] In addition, the present invention also solves the problem of dispersion stability of nanographene sheets in water-based drilling fluids. By optimizing the surface modification technology of nanographene sheets, the dispersion of nanographene sheets in high mineralization environments is enhanced, thereby improving the application performance of plugging materials under extreme conditions.

[0008] Ultimately, the present invention achieves the successful transformation of oil-based drilling fluid to water-based drilling fluid in shale gas drilling, which not only improves drilling efficiency but also reduces the impact on the environment, providing important technical support for the efficient development of shale gas resources.

[0009] In order to achieve the above objectives, the first aspect of the present invention provides a method for preparing a two-dimensional nanographene sheet, the method comprising:

[0010] (1) uniformly mixing raw graphite and an activator to perform a first reaction to obtain an activated graphite dispersion;

[0011] (2) slowly adding the activated graphite dispersion to an oxidant, heating the mixture in a temperature-controlled water bath, and maintaining the temperature for a certain period of time to obtain a two-dimensional nanographene sheet pre-product;

[0012] (3) After the graphene pre-product is washed with deionized water until it is neutral, ultrasonic treatment is performed in deionized water to obtain a two-dimensional nanographene sheet dispersion.

[0013] The second aspect of the present invention provides a two-dimensional nanographene sheet prepared by the method described in the first aspect.

[0014] The third aspect of the present invention provides the use of the two-dimensional nanographene sheets described in the second aspect as plugging agents in water-based drilling fluids.

[0015] The fourth aspect of the present invention provides a water-based drilling fluid, which contains the two-dimensional nanographene sheets described in the second aspect.

[0016] Through the above technical solution, the present invention can achieve the following beneficial effects:

[0017] (1) The two-dimensional nanographene sheet prepared by the method of the present invention has good hydrophilicity, an average number of layers of 2-20 layers, an average particle size of 264-852nm, good dispersibility in water-based drilling fluid, and is not easy to agglomerate. Its excellent pressure bearing capacity enables it to effectively block the nano-scale pores in the shale formation at a relatively low concentration, delay the transmission of pore pressure, and thus improve the pressure bearing capacity of the formation.

[0018] (2) The water-based drilling fluid provided by the present invention contains the above-mentioned high-quality two-dimensional nanographene sheets, exhibits good rheological properties and high plugging rate, and has strong environmental adaptability. The water-based drilling fluid can significantly improve the stability of the well wall, effectively protect the reservoir, and thus optimize the overall efficiency of shale gas drilling operations. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the result of particle size analysis of plugging agent S1.

[0020] Figure 2 This is a transmission electron microscope photo of plugging agent S1. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The specific implementation of the present invention is described in detail below. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0023] The first aspect of the present invention provides a method for preparing a two-dimensional nanographene sheet, the method comprising:

[0024] (1) uniformly mixing raw graphite and an activator to perform a first reaction to obtain an activated graphite dispersion;

[0025] (2) slowly adding the activated graphite dispersion to an oxidant, heating the mixture in a temperature-controlled water bath, and maintaining the temperature for a certain period of time to obtain a two-dimensional nanographene sheet pre-product;

[0026] (3) After washing the two-dimensional nanographene sheet pre-product with deionized water until it is neutral, ultrasonic treatment is performed in deionized water to obtain a two-dimensional nanographene sheet dispersion.

[0027] According to the invention of this patent, in step (1), the raw graphite and the activator are uniformly mixed to carry out a first reaction, and the activator activates the raw graphite by oxidation to obtain activated fluffy graphite, namely the activated graphite dispersion.

[0028] According to the invention of this patent, the raw graphite is preferably natural flake graphite. Preferably, the natural flake graphite has a particle size in the range of 200-400 mesh and a purity greater than 99%.

[0029] According to the invention of this patent, preferably, the activator is selected from one of perglacial acetic acid, citric acid and phosphoric acid, preferably glacial acetic acid.

[0030] According to the present invention, preferably, the oxidant is selected from one of hydrogen peroxide, peracetic acid and sodium peroxide, and more preferably hydrogen peroxide.

[0031] According to the invention of this patent, in step (1), in order to obtain better oxidation activation and effect of raw graphite, preferably, the weight ratio of raw graphite: activator is 1: (15-35), preferably 1: (20-30).

[0032] According to the invention of this patent, in step (1), the first reaction is carried out at room temperature. The reaction system consisting of the raw graphite and the activator undergoes oxidation activation of the graphite at the temperature required for the first reaction.

[0033] According to the invention of this patent, in step (1), the operation process of the first reaction includes: at room temperature, mixing the raw graphite and the activator according to the above-mentioned weight ratio to obtain a uniform mixture, the mixing time is preferably 6-10s, and the first reaction is completed.

[0034] According to the invention of this patent, in step (1), after the first reaction is completed, a first product system containing activated graphite is obtained.

[0035] In this patent invention, room temperature refers to 20-25°C.

[0036] According to the invention of this patent, in step (2), the activated graphite dispersion is fully oxidized under the action of an oxidant to separate the activated graphite and obtain a two-dimensional nanographene sheet pre-product.

[0037] According to the present invention, in step (2), preferably, the oxidant is selected from at least one of hydrogen peroxide, peracetic acid and sodium peroxide, and more preferably hydrogen peroxide.

[0038] According to the invention of this patent, in step (2), in order to obtain a better exfoliation effect, preferably, the weight ratio of the activated graphite dispersion: oxidant is 1: (0.25-0.55), preferably 1: (0.35-0.45).

[0039] According to the invention of this patent, in step (2), the conditions of the second reaction include: temperature of 30-50°C, time of 2-4h;

[0040] According to the invention of this patent, in step (2), after the second reaction is completed, the two-dimensional nanographene sheet pre-product is obtained.

[0041] According to the invention of this patent, in step (3), the two-dimensional nanographene sheet pre-product is washed with deionized water until it is neutral, and then ultrasonically treated in deionized water to obtain a two-dimensional nanographene sheet dispersion.

[0042] According to the invention of this patent, in step (3), the conditions of the ultrasonic treatment include: time of 1-2 hours, power of 200-400W, ensuring that the solution temperature does not exceed 50°C during the treatment process.

[0043] The average number of layers of the two-dimensional nanographene sheets is 2-20, preferably 5-15; the average particle size of the two-dimensional nanographene sheets is 264-852nm, preferably 300-800nm.

[0044] The second aspect of the present invention provides a two-dimensional nanographene sheet prepared by the method described in the first aspect, wherein the average number of layers of the two-dimensional nanographene sheet is 2-20 layers, preferably 5-15 layers.

[0045] According to the invention of this patent, the average particle size of the two-dimensional nanographene sheet is 264-852nm, preferably 300-800nm, which meets the requirements for sealing microcracks in the formation in terms of size.

[0046] According to the invention of this patent, the two-dimensional nanographene sheet has strong hydrophilicity, can be well dispersed in the water phase, is not easy to agglomerate in the water-based drilling fluid system, has a good dispersion effect, and can achieve excellent plugging effect at a lower concentration, thereby reducing the formation permeability and preventing drilling fluid intrusion.

[0047] According to the invention of this patent, the two-dimensional nanographene sheet has a strong pressure-bearing capacity, can delay the transmission of pore pressure in the formation, and improve the pressure-bearing capacity of the formation.

[0048] According to the invention of this patent, the two-dimensional nanographene sheet has little effect on the viscosity and shear force of the water-based drilling fluid, has good compatibility and strong adaptability.

[0049] The third aspect of the present invention provides the use of the two-dimensional nanographene sheets described in the second aspect as plugging agents in water-based drilling fluids.

[0050] The fourth aspect of the present invention provides a water-based drilling fluid, which contains the two-dimensional nanographene sheets described in the second aspect.

[0051] According to the invention of this patent, the water-based drilling fluid includes the following components: 100 parts by weight of base fluid, 5-12 parts by weight of bentonite, 0.2-0.9 parts by weight of polymer tackifier, 2.0-8.0 parts by weight of fluid loss reducer, 1.5-6.0 parts by weight of conventional plugging agent, 1.5-3.5 parts by weight of lubricant, 1.0-6.0 parts by weight of inhibitor, 0.3-2.0 parts by weight of pH regulator, 0.25-1.0 parts by weight of nano plugging agent, and 80-300 parts by weight of weighting agent;

[0052] According to the invention of this patent, the water-based drilling fluid, on the basis of satisfying the above composition, preferably, comprises the following components: 100 parts by weight of base fluid, 6.5-10.0 parts by weight of bentonite, 0.4-0.7 parts by weight of polymer tackifier, 3.5.0-6.0 parts by weight of fluid loss reducer, 4.0-5.0 parts by weight of conventional plugging agent, 2.0-3.0 parts by weight of lubricant, 3.0-5.0 parts by weight of inhibitor, 0.6-1.4 parts by weight of pH adjuster, 0.3-0.75 parts by weight of nano plugging agent, 160-240 parts by weight of weighting agent;

[0053] According to the invention of this patent, the base liquid is tap water, and the invention of this patent has no special limitation on this.

[0054] According to the present invention, the bentonite is at least one of sodium-based bentonite, calcium-based bentonite and calcium-sodium-based bentonite, and more preferably sodium-based bentonite. In the present invention, the sodium-based bentonite can be obtained by self-production using conventional methods in the art, or it can be a conventional commercially available product, and the present invention has no particular limitation on this.

[0055] According to the invention of this patent, the polymer thickener is selected from at least carboxymethyl cellulose, polyanionic cellulose, magnetic polyacrylamide and guar gum, and is more preferably carboxymethyl cellulose. The carboxymethyl cellulose can be divided into low-viscosity carboxymethyl cellulose (viscosity range: 10-200mPa·s), medium-viscosity carboxymethyl cellulose (viscosity range: 200-1500mPa·s), and high-viscosity carboxymethyl cellulose (viscosity range: 1500-5000mPa·s) according to viscosity, and is more preferably medium-viscosity carboxymethyl cellulose.

[0056] According to the invention of this patent, the fluid loss reducer is selected from at least carboxymethyl starch, sulfonated lignin, acrylamide / sodium acrylate copolymer and polyvinyl alcohol, and carboxymethyl starch is more preferred. The carboxymethyl starch can be divided into low-substituted carboxymethyl starch (substitution degree: 0.1-0.3), medium-substituted carboxymethyl starch (substitution degree: 0.3-0.5), and high-substituted carboxymethyl starch (substitution degree: 0.5 or more) according to the degree of substitution, and high-substituted carboxymethyl starch is more preferred.

[0057] According to the invention of this patent, the conventional plugging agent is selected from at least fine-grained limestone, cellulose fiber, modified paraffin and calcium carbonate / high-toughness resin composite, and more preferably calcium carbonate / high-toughness resin composite. In the invention of this patent, the fluid loss reducer can be obtained by self-preparation using conventional methods in the art, or can be a conventional commercially available brand product, and the invention of this patent has no special limitation on this.

[0058] According to the invention of this patent, the weighting agent can be a conventional weighting agent for drilling fluid in the art. Preferably, the weighting agent is selected from at least one of API barite, ultrafine barium sulfate, magnetite powder, ilmenite powder and manganese tetraoxide, and more preferably API barite.

[0059] The water-based drilling fluid system provided by this patent invention effectively seals formation cracks and micropores, prevents hydration and expansion of clay minerals in shale formations after reacting with water, helps to enhance wellbore stability and reduce the risk of wellbore collapse; effectively controls drilling fluid filtration loss, prevents mud filtrate from entering the formation, and protects the reservoir; helps to carry drill cuttings, improve drilling efficiency, and ensure well bottom cleanliness; these advantages make the water-based drilling fluid have excellent performance in shale gas drilling, can effectively cope with complex formation environments, and improve drilling efficiency and operation safety.

[0060] The invention of this patent will be described in detail below through examples. In the following preparation examples, embodiments and comparative examples,

[0061] Base fluid: tap water;

[0062] Bentonite: sodium bentonite, purchased from Qingdao Runtu Bentonite Co., Ltd.;

[0063] Polymer thickener: medium viscosity carboxymethyl cellulose, purchased from Qingdao Runtu Bentonite Co., Ltd.;

[0064] Fluid loss reducer: carboxymethyl starch, purchased from Hebei Yanxing Chemical Co., Ltd.;

[0065] Conventional plugging agent: calcium carbonate / high-toughness resin composite, purchased from Sichuan Southwest Shida Technology Co., Ltd.;

[0066] Commercially available nano plugging agents: silicon dioxide, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0067] Unless otherwise specified, other materials used are common commercially available products.

[0068] Preparation Example 1

[0069] (1) natural flake graphite (300 mesh, purity 99%) and glacial acetic acid were placed in a flask at a weight ratio of 1:25 and stirred for 10 seconds to obtain an activated graphite dispersion;

[0070] (2) under electromagnetic stirring, adding hydrogen peroxide to the activated graphite dispersion at a weight ratio of 0.4:1 to obtain a mixed solution, heating the mixed solution to 40° C. in a temperature-controlled water bath, and maintaining the temperature for 3 hours to obtain a two-dimensional nanographene sheet pre-product;

[0071] (3) After the two-dimensional nanographene sheet pre-product is washed with deionized water until it is neutral, ultrasonic treatment is performed in deionized water (power is 300 W, temperature is room temperature) to obtain a two-dimensional nanographene sheet dispersion (denoted as S1).

[0072] Preparation Example 2

[0073] (1) natural flake graphite (300 mesh, purity 99%) and glacial acetic acid were placed in a flask at a weight ratio of 1:20 and stirred for 10 seconds to obtain an activated graphite dispersion;

[0074] (2) under electromagnetic stirring, adding hydrogen peroxide to the activated graphite dispersion at a weight ratio of 0.45:1 to obtain a mixed solution, heating the mixed solution to 50° C. in a temperature-controlled water bath, and maintaining the temperature for 4 hours to obtain a two-dimensional nanographene sheet pre-product;

[0075] (3) After the two-dimensional nanographene sheet pre-product is washed with deionized water until it is neutral, ultrasonic treatment is performed in deionized water (power is 400 W, temperature is room temperature) to obtain a two-dimensional nanographene sheet dispersion (denoted as S2).

[0076] Preparation Example 3

[0077] (1) natural flake graphite (300 mesh, purity 99%) and glacial acetic acid were placed in a flask at a weight ratio of 1:40 and stirred for 10 seconds to obtain an activated graphite dispersion;

[0078] (2) under electromagnetic stirring, adding hydrogen peroxide to the activated graphite dispersion at a weight ratio of 0.50:1 to obtain a mixed solution, heating the mixed solution to 60° C. in a temperature-controlled water bath, and maintaining the temperature for 5 hours to obtain a two-dimensional nanographene sheet pre-product;

[0079] (3) After the two-dimensional nanographene sheet pre-product is washed with deionized water until it is neutral, ultrasonic treatment is performed in deionized water (power is 500 W, temperature is 60° C.) to obtain a two-dimensional nanographene sheet dispersion (denoted as S3).

[0080] Example 1

[0081] 100 parts by weight of tap water and 8 parts by weight of bentonite were stirred at a stirring rate of 1000 r / min for 60 min and then allowed to stand for 24 h. Then 0.6 parts by weight of polymer tackifier was added and stirred at a stirring rate of 2000 r / min for 30 min. Then 4.5 parts by weight of fluid loss reducer was stirred at a stirring rate of 2000 r / min for 20 min. Then 4.5 parts by weight of conventional plugging agent was added and stirred at a stirring rate of 2000 r / min for 10 min. Then 2.5 parts by weight of lubricant was added and stirred at 1000 r / min for 30 min. r / min and stirred for 10 min, then 4.0 parts by weight of an inhibitor was added and stirred at a stirring rate of 2000 r / min for 10 min, then 1.0 parts by weight of a pH adjuster was added and stirred at a stirring rate of 1000 r / min for 10 min, then 0.5 parts by weight of nano plugging agent S1 was added and stirred at a stirring rate of 2000 r / min for 30 min, then 200 parts by weight of a weighting agent was added and stirred at a stirring rate of 2000 r / min for 30 min to obtain a water-based drilling fluid (denoted as F1).

[0082] The components and contents of F1 are shown in Table 1.

[0083] Example 2-3

[0084] The method of Example 1 is followed, except that S2 and S3 are used as plugging agents, respectively, and other conditions are the same as those of Example 1. Water-based drilling fluids (respectively denoted as F2 and F3) are obtained.

[0085] Example 4

[0086] 100 parts by weight of tap water and 10 parts by weight of bentonite were stirred at a stirring rate of 1000 r / min for 60 min and then allowed to stand for 24 h. Then, 0.7 parts by weight of polymer viscosity enhancer was added and stirred at a stirring rate of 2000 r / min for 30 min. Then, 6.0 parts by weight of fluid loss reducer was added and stirred at a stirring rate of 2000 r / min for 20 min. Then, 5.0 parts by weight of conventional plugging agent was added and stirred at a stirring rate of 2000 r / min for 10 min. Then, 3.0 parts by weight of lubricant was added and stirred at 1000 r / min for 30 min. r / min and stirred for 10 min, then 5.0 parts by weight of an inhibitor was added and stirred at a stirring rate of 2000 r / min for 10 min, then 1.4 parts by weight of a pH adjuster was added and stirred at a stirring rate of 1000 r / min for 10 min, then 0.75 parts by weight of nano plugging agent S1 was added and stirred at a stirring rate of 2000 r / min for 30 min, then 240 parts by weight of a weighting agent was added and stirred at a stirring rate of 2000 r / min for 30 min, to obtain a water-based drilling fluid (denoted as F4).

[0087] The components and contents of F4 are shown in Table 1.

[0088] Embodiment 5-6

[0089] The method of Example 4 is followed, except that S2 and S3 are used as plugging agents, respectively, and other conditions are the same as those of Example 4. Water-based drilling fluids (respectively denoted as F5 and F6) are obtained.

[0090] Example 7

[0091] 100 parts by weight of tap water and 5 parts by weight of bentonite were stirred at a stirring rate of 1000 r / min for 60 min and then allowed to stand for 24 h. Then 0.2 parts by weight of polymer viscosity enhancer was added and stirred at a stirring rate of 2000 r / min for 30 min. Then 2.0 parts by weight of fluid loss reducer was added and stirred at a stirring rate of 2000 r / min for 20 min. Then 1.5 parts by weight of conventional plugging agent was added and stirred at a stirring rate of 2000 r / min for 10 min. Then 1.5 parts by weight of lubricant was added and stirred at a stirring rate of 1000 r / min. r / min and stirred for 10 min, then 1.0 weight part of inhibitor was added and stirred at a stirring rate of 2000 r / min for 10 min, then 0.3 weight part of pH adjuster was added and stirred at a stirring rate of 1000 r / min for 10 min, then 0.25 weight part of nano plugging agent S1 was added and stirred at a stirring rate of 2000 r / min for 30 min, then 80 weight parts of weighting agent was added and stirred at a stirring rate of 2000 r / min for 30 min to obtain a water-based drilling fluid (denoted as F7).

[0092] The components and contents of F7 are shown in Table 1.

[0093] Embodiment 8-9

[0094] The method of Example 7 is followed, except that S2 and S3 are used as plugging agents, respectively, and other conditions are the same as those of Example 7. Water-based drilling fluids (respectively denoted as F8 and F9) are obtained.

[0095] Example 10

[0096] 100 parts by weight of tap water and 12 parts by weight of bentonite were stirred at a stirring rate of 1000 r / min for 60 min and then allowed to stand for 24 h. Then 0.9 parts by weight of polymer viscosity enhancer was added and stirred at a stirring rate of 2000 r / min for 30 min. Then 8.0 parts by weight of fluid loss reducer was added and stirred at a stirring rate of 2000 r / min for 20 min. Then 6.0 parts by weight of conventional plugging agent was added and stirred at a stirring rate of 2000 r / min for 10 min. Then 3.5 parts by weight of lubricant was added and stirred at 1000 r / min for 30 min. r / min and stirred for 10 min, then 6.0 parts by weight of an inhibitor was added and stirred at a stirring rate of 2000 r / min for 10 min, then 2.0 parts by weight of a pH adjuster was added and stirred at a stirring rate of 1000 r / min for 10 min, then 1.0 parts by weight of a nano plugging agent S1 was added and stirred at a stirring rate of 2000 r / min for 30 min, then 300 parts by weight of a weighting agent was added and stirred at a stirring rate of 2000 r / min for 30 min, to obtain a water-based drilling fluid (denoted as F10).

[0097] The components and contents of F10 are shown in Table 1.

[0098] Examples 11-12

[0099] The method of Example 10 is followed, except that S2 and S3 are used as plugging agents, respectively, and other conditions are the same as those of Example 10. Water-based drilling fluids (respectively denoted as F11 and F12) are obtained.

[0100] Comparative Example 1

[0101] The method of Example 1 is followed, except that the plugging agent S1 is not added, and other conditions are the same as those of Example 1. A water-based drilling fluid (denoted as DF1) is obtained.

[0102] Comparative Example 2

[0103] The method of Example 1 is followed, except that the two-dimensional nanographene sheet pre-product obtained in step (2) of Preparation Example 1 is used as the plugging agent, and other conditions are the same as those of Example 1. A water-based drilling fluid (denoted as DF2) is obtained.

[0104] Comparative Example 3

[0105] The method of Example 2 is followed, except that the two-dimensional nanographene sheet pre-product obtained in step (2) of Preparation Example 2 is used as the plugging agent, and other conditions are the same as those of Example 2. A water-based drilling fluid (denoted as DF3) is obtained.

[0106] Comparative Example 4

[0107] The method of Example 3 is followed, except that the two-dimensional nanographene sheet pre-product obtained in step (2) of Preparation Example 3 is used as the plugging agent, and other conditions are the same as those of Example 3. A water-based drilling fluid (denoted as DF4) is obtained.

[0108] Comparative Example 5

[0109] The method of Example 1 is followed, except that S1 is replaced by natural flake graphite, and other conditions are the same as those of Example 1. A water-based drilling fluid (denoted as DF5) is obtained.

[0110] Comparative Example 6

[0111] The method of Example 1 is followed, except that S1 is replaced by commercially available nano-silicon dioxide, and other conditions are the same as those of Example 1. A water-based drilling fluid (denoted as DF6) is obtained.

[0112] Comparative Example 7

[0113] The method of Example 1 was followed, except that the amount of S1 added was adjusted to 2.0 parts by weight, and the other conditions were the same as those of Example 1. A water-based drilling fluid (denoted as DF7) was obtained.

[0114] Table 1

[0115]

[0116] Table 1

[0117]

[0118] Note: In Table 1, the two-dimensional nanographene sheet pre-products used in DF2-DF4 are the two-dimensional nanographene sheet pre-products prepared in step (2) of Preparation Examples 1-3, respectively.

[0119] Test Case

[0120] The two-dimensional nanographene sheet products S1-S3 prepared in Preparation Examples 1-3 were subjected to particle size tests, average layer number tests and contact angle tests to evaluate their hydrophilicity and dispersibility, and the water-based drilling fluids F1-F12 prepared in Examples 1-12 and the water-based drilling fluids DF1-DF7 prepared in Comparative Examples 1-7 were tested for plugging performance, pressure bearing performance and compatibility performance. In the following test examples,

[0121] Apparent viscosity (AV, mPa·s), plastic viscosity (PV, mPa·s), and dynamic shear force (YP, Pa) were measured using a six-speed rotary viscometer according to the method specified in GB / T29170-2012;

[0122] Medium pressure filtration loss (API, mL) was measured using a medium pressure filtration instrument according to the method specified in GB / T29170-2012;

[0123] High temperature and high pressure filtration loss (HTHP, mL) is measured using a high temperature and high pressure filtration instrument according to the method specified in GB / T29170-2012;

[0124] The manufacturer of the laser particle size analyzer is Malvern Instruments of the United Kingdom;

[0125] The manufacturer of the contact angle measuring instrument is Chengdu Snow Leopard Technology Co., Ltd., model SDC-350;

[0126] The manufacturer of the six-speed rotational viscometer is Stillbo Company, model ZNN-D6S;

[0127] The manufacturer of the medium-pressure filter loss meter is Steele Platt Company, model SD4 / SD4A;

[0128] The manufacturer of the high-temperature and high-pressure filtration tester is Kence Instruments, model KC-GS173.

[0129] 1. Particle size, average number of layers and contact angle

[0130] Particle size test: Add plugging agent S1 into deionized water, stir thoroughly, and use a laser particle size analyzer to measure the particle size of the plugging agent after it is dispersed in deionized water, and observe its dispersion degree.

[0131] The results are as follows Figure 1 , as shown in Table 2.

[0132] Average layer number test: In order to directly observe the microstructure such as the number of layers of the two-dimensional nanographene sheets, the obtained graphene nanosheets were ultrasonically dispersed in deionized water using a cell crusher and observed using TEM analysis.

[0133] The results are as follows Figure 2 , as shown in Table 2.

[0134] Contact angle test: 300 mg of plugging agents S1-S3 were weighed respectively, and made into sample slices using a tablet press. The contact angle of distilled water on the surface of the slices was measured using a contact angle meter.

[0135] The results are shown in Table 2.

[0136] Table 2

[0137]

[0138] It can be seen from Table 2 that the particle size of S1-S3 is in the range of 282-335nm, the contact angle with distilled water is completely spread out, and no agglomeration occurs in deionized water, which indicates that the two-dimensional nanographene sheets prepared by the present invention have excellent dispersibility in the aqueous phase and do not agglomerate, so that they can be dispersed in nanometer size in the oil phase, thereby meeting the requirements for plugging the micropores in the shale formation.

[0139] 2. Sealing performance

[0140] The base slurry (tap water + 6% bentonite + 5% sodium carbonate + 5% SMC-Ⅰ + 10% SMC-Ⅱ + 10% nanobarite, where the percentage of each component is based on the weight of tap water) is placed in a high-temperature and high-pressure filter loss tester, and the high-temperature and high-pressure filter loss test is carried out for 60 minutes at 105°C and a pressure difference of 3.5MPa. After the test, it is cooled to room temperature, the base slurry in the mud cup is poured out, and the filter cake is left at the bottom of the mud cup; deionized water is injected along the inner wall of the mud cup 1-2 times and gently shaken during the injection process. Then, the deionized water was poured out to wash away the virtual mud on the filter cake; the deionized water was then injected into the mud cup to the scale, and the high temperature and high pressure filtration loss test process was repeated under the conditions of a temperature of 105°C and a pressure difference of 3.5 MPa for 30 minutes to further wash away the virtual mud. After the test, the mud was cooled to room temperature, the deionized water was poured out, and the mud cake in the mud cup was taken out. The permeability of the base mud was calculated to be 5.821×10-4mD using formula (I); the base mud cake was used as a simulated formation with micro-nano fractures;

[0141] K0=q·l·μ / (A·ΔP)(I)

[0142] Where, K0: permeability, mD;

[0143] q: average filtration loss per unit time, cm3 / s;

[0144] l: mud cake thickness, mm;

[0145] μ: drilling fluid viscosity, mPa·s;

[0146] A: mud cake area, m2;

[0147] ΔP: pressure difference, MPa

[0148] Drilling fluids F1-F12 and DF1-DF7 were used as test slurries for aging treatment (aging temperature was 105°C, aging time was 16h), and after cooling to room temperature, they were placed in the mud cups of the high-temperature and high-pressure filter loss instrument (the base slurry cake at the bottom of the mud cup was used as the filtration medium), and the high-temperature and high-pressure filter loss test was carried out for 30 minutes at a temperature of 105°C and a pressure difference of 3.5MPa. After the test, they were cooled to room temperature, the slurry in the mud cup was poured out, and the test slurry cake was left at the bottom of the mud cup; deionized water was injected along the inner wall of the mud cup 1-2 times and gently shaken during the injection process, and then the deionized water was poured out to wash away the virtual mud on the filter cake; deionized water was then injected into the mud cup to the scale. The above high temperature and high pressure filtration loss test process was repeated under the conditions of temperature of 105°C and pressure difference of 3.5MPa. The test time was 30min to further wash away the false mud. After the test, it was cooled to room temperature, deionized water was poured out, and the test slurry mud cake in the mud cup was taken out. The mud cake permeability of the test slurries F1-F12 and DF1-DF7 was calculated according to the above formula (I) (denoted as K1, mD). On this basis, the permeability reduction rate of the test slurries F1-F12 and DF1-DF7 before and after plugging the simulated formation was calculated using formula (II) (that is, the permeability reduction rate was used to characterize the plugging effect. The higher the permeability reduction rate, the better the plugging effect of the plugging material). The results are shown in Table 3.

[0149]

[0150] Where, Kr: permeability reduction rate, %;

[0151] K0: permeability of base mud cake (simulated formation), mD;

[0152] K1: Permeability of water-based drilling fluid cake, mD

[0153] Table 3

[0154] Water-based drilling fluid <![CDATA[Permeability (10 -4 mD)]]> Blockage rate F1 0.021 99.64% F2 0.042 99.28% F3 0.053 99.09% F4 0.079 98.64% F5 0.112 98.08% F6 0.157 97.30% F7 0.084 98.56% F8 0.096 98.35% F9 0.098 98.32% F10 0.147 97.47% F11 0.112 98.08% F12 0.162 97.22% DF1 3.023 48.07% DF2 3.038 47.81% DF3 3.122 46.37% DF4 4.088 29.77% DF5 3.486 40.11% DF6 3.088 46.95% DF7 2.070 64.44%

[0155] As can be seen from Table 3, through simulation tests, water-based drilling fluids F1-F12 use the two-dimensional nanographene sheets provided by the invention of this patent as plugging agents, which can effectively plug micro-nano cracks in simulated formations, showing excellent plugging performance, and the permeability reduction rate is greater than 97%. However, water-based drilling fluid DF1 does not use plugging agents, DF2-DF4 use plugging agents that are not prepared according to the method of the invention of this patent, and DF5+DF6 use conventional commercial plugging agents or natural flake graphite as plugging agents, and the plugging effects are significantly worse than F1+F12. The excellent plugging performance obtained by F1-F12 is due to the fact that the two-dimensional nanographene sheet plugging agents used have good hydrophilicity, can be evenly dispersed in the water-based drilling fluid system, and have a suitable size and good pressure-bearing performance, thereby effectively plugging micro-nano cracks, reducing formation permeability, and preventing drilling fluid from invading the formation. In particular, DF7 does not adopt the water-based drilling fluid formula of the present application, and its plugging performance is somewhat inferior to that of F1-F12.

[0156] 3. Pressure bearing performance

[0157] The 3D printed core was loaded into the formation micro-fracture plugging and pressure bearing capacity evaluation device, and the above-mentioned drilling fluids F1-F12 and DF1-DF7 were added into the device at 120°C, respectively. Starting from 0 MPa, the pressure was increased with a gradient of 0.5 MPa, and the pressure was maintained for 3 minutes each time until the pressure was increased to 6 MPa and maintained for 3 minutes. During this process, the amount of drilling fluid (i.e., the amount of filtrate) driven out under different pressures is shown in Table 4.

[0158] Table 4

[0159]

[0160] As can be seen from Table 4, in the test of micro-fracture plugging and pressure bearing capacity evaluation of the formation, the water-based drilling fluid F1-F12 can withstand a pressure of 30 MPa, showing excellent pressure bearing performance, which is conducive to delaying the transmission of pore pressure and improving the pressure bearing capacity of the formation. In contrast, the pressure bearing performance of DF1-DF7 is poor.

[0161] 4. Compatibility

[0162] Prepare water-based drilling fluid A (tap water + 8% bentonite + 0.6% polymer viscosity enhancer + 4.5% fluid loss reducer + 4.5% conventional plugging agent + 2.5% lubricant + 4% inhibitor + 1% pH adjuster, wherein the percentage of each component is based on the weight of tap water), and then add 0.5% (based on the weight of tap water in the water-based drilling fluid A) of the two-dimensional nanographene sheet S1 prepared in Preparation Example 1 to the above-mentioned water-based drilling fluid A to prepare water-based drilling fluid B.

[0163] Table 5

[0164]

[0165] It can be seen from Table 5 that the addition of the two-dimensional nanographene sheet plugging agent of the present invention has little effect on the rheological properties of the water-based drilling fluid, and the rheological properties are good, indicating that the two-dimensional nanographene sheet provided by the present invention has good compatibility as a plugging agent for water-based drilling fluid.

[0166] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A preparation method of a two-dimensional nanographene sheet and its application in a water-based drilling fluid, characterized in that: The method includes: (1) uniformly mixing raw graphite and an activator to perform a first reaction to obtain an activated graphite dispersion; (2) slowly adding the activated graphite dispersion to an oxidant, heating the mixture in a temperature-controlled water bath, and maintaining the temperature for a certain period of time to obtain a two-dimensional nanographene sheet pre-product; (3) After washing the two-dimensional nanographene sheet pre-product with deionized water until it is neutral, ultrasonic treatment is performed in deionized water to obtain a two-dimensional nanographene sheet dispersion.

2. The method according to claim 1, wherein: In step (1), the weight ratio of the raw graphite:activator is 1:(15-35), preferably 1:(20-30).

3. The method according to claim 1 or 2, wherein: In step (2), the weight ratio of the activated graphite dispersion: oxidant is 1: (0.25-0.55), preferably 1: (0.35-0.45).

4. The method according to any one of claims 1 to 3, wherein: The activator is selected from one of perglacial acetic acid, citric acid and phosphoric acid, preferably glacial acetic acid; Preferably, the oxidant is at least one selected from hydrogen peroxide, peracetic acid and sodium peroxide, and more preferably hydrogen peroxide.

5. The method according to any one of claims 1 to 4, wherein: In step (1), the conditions of the first reaction include: the temperature is room temperature; Preferably, in step (2), the conditions of the second reaction include: temperature of 30-50°C and time of 2-4h; Preferably, in step (3), the conditions of the ultrasonic treatment include: a time of 1-2 hours, a power of 200-400W, and ensuring that the solution temperature does not exceed 50°C during the treatment.

6. A two-dimensional nanographene sheet obtained by the preparation method according to any one of claims 1 to 5, wherein: The average number of layers of the two-dimensional nanographene sheets is 2-20, preferably 5-15; the average particle size of the two-dimensional nanographene sheets is 264-852nm, preferably 300-800nm.

7. Use of the two-dimensional nanographene sheet according to claim 6 as a plugging agent in a water-based drilling fluid.

8. A water-based drilling fluid comprising the two-dimensional nanographene sheet according to claim 6.

9. The water-based drilling fluid according to claim 8, wherein: The water-based drilling fluid comprises the following components: 100 parts by weight of base fluid, 5-12 parts by weight of bentonite, 0.2-0.9 parts by weight of polymer tackifier, 2.0-8.0 parts by weight of fluid loss reducer, 1.5-6.0 parts by weight of conventional plugging agent, 1.5-3.5 parts by weight of lubricant, 1.0-6.0 parts by weight of inhibitor, 0.3-2.0 parts by weight of pH regulator, 0.25-1.0 parts by weight of nano plugging agent, and 80-300 parts by weight of weighting agent; Preferably, the water-based drilling fluid comprises the following components: 100 parts by weight of base fluid, 6.5-10.0 parts by weight of bentonite, 0.4-0.7 parts by weight of polymer viscosity enhancer, 3.5.0-6.0 parts by weight of fluid loss reducer, 4.0-5.0 parts by weight of conventional plugging agent, 2.0-3.0 parts by weight of lubricant, 3.0-5.0 parts by weight of inhibitor, 0.6-1.4 parts by weight of pH adjuster, 0.3-0.75 parts by weight of nano plugging agent, and 160-240 parts by weight of weighting agent.

10. The water-based drilling fluid according to claim 8 or 9, wherein: The base liquid is tap water; Preferably, the bentonite is at least one of sodium-based bentonite, calcium-based bentonite and calcium-sodium-based bentonite, and more preferably sodium-based bentonite; Preferably, the polymer thickener is selected from at least one of carboxymethyl cellulose, polyanionic cellulose, magnetic polyacrylamide and guar gum, and more preferably carboxymethyl cellulose; Preferably, the fluid loss reducer is selected from at least one of carboxymethyl starch, sulfonated lignin, acrylamide / sodium acrylate copolymer and polyvinyl alcohol, and more preferably carboxymethyl starch; Preferably, the conventional plugging agent is selected from at least one of fine-grained limestone, cellulose fiber, modified paraffin wax and calcium carbonate / high-toughness resin composite, and more preferably calcium carbonate / high-toughness resin composite; Preferably, the lubricant is selected from at least one of mineral oil, diesel, synthetic ester, polyethylene glycol and graphite, and more preferably graphite; Preferably, the inhibitor is selected from at least potassium chloride, ethylenediamine, polyamine, sodium formate and triethanolamine, and more preferably potassium chloride; Preferably, the pH adjuster is at least one selected from sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate, and more preferably sodium carbonate.

Citation Information

Patent Citations

  • Preparing method of oxidized graphene and high-conductivity graphene

    CN106564891A

  • Strong-suppression strong-sealing water-based drilling fluid suitable for shale formations, and preparation method thereof

    CN109837072A

  • High-plugging-performance drilling fluid composition and preparation method and application thereof

    CN110205104A

  • Chitosan and graphene oxide nano-hydrogel plugging agent and water-based drilling fluid

    CN111808581A

  • Polysulfonic acid silane composite graphene oxide plugging agent and oil-based drilling fluid

    CN114605976A